(untitled) (Innovate Conferences, 2025)
Endovascular surgery techniques are widely used in various fields of medicine, including neurosurgery. The main X-ray angiosurgical interventions in neurosurgery are cerebral angiography, coiling of arterial aneurysms, embolization of arteriovenous malformations, and stenting of vessels. Anesthetic support for these operations has certain features. Since the operations are low-traumatic and not accompanied by severe pain, anesthetic aggression should be minimal. To ensure high precision of the surgeon’s work, a deep controlled neuromuscular block is necessary. The use of a laryngeal mask, a low degree of analgesia, deep sleep, and sufficient muscle relaxation under the control of TOF monitoring fully satisfy these requirements. This technique was used for anesthetic support for endovascular interventions in the neuroreanimation department of the Russian Scientific Center for Emergency Medicine of the Astrakhan Region.